International arbitration and international public policy. Mandatory rule and anationality. - Zappalá, Francesco (2019)
It is conceptually impossible speak of international public policy by adding the “French” adjective or “Portuguese”, because in this case, is no longer international public policy but it is public policy of the State of the adjective. The state judge exercises control from the perspective of the principles that govern its own internal order and, therefore, has no competence in the broad sense of the term, to provide for the implementation of the international public policy.